ENHANCED NOMA OPTIMIZATION USING BLUE WHALE ALGORITHM FOR BER AND SPECTRAL EFFICIENCY ENHANCEMENT (Global Journal of Advanced Engineering Technologies and Sciences, 2025)
Non-Orthogonal Multiple Access (NOMA) is referred to as a disruptive technology in the 5G and future technology wireless networks on traffic capabilities that require massive connectivity and better spectral efficiency. Power allocation among users plays an important role in significantly determining the performance of NOMA, especially, in high spectral efficiency. This paper suggests an Enhanced NOMA scheme that is optimized by using the Blue Whale Optimization (BWO) scheme. The proposed methodology seeks to optimize the Bit Error Rate (BER) and Spectral Efficiency (SE) by dynamic power coefficients of the users. Under both Rayleigh and Rician fading conditions, simulations indicate that the proposed BWO-optimized NOMA system has a large gain compared to conventional power allocation schemes and other all heuristic-based system, in terms of both BER and SE performances.